How to draw learn to draw step by step - Foster, Walter T. (Walter Thomas) 1891-1981 (California, usa Walter Foster Publishing, 2011)
preparing to draw - blocking in basic shapes creating simple textures - beginning shading
13
Keywords: Drawing -- Technique